Koreksi Paulus terhadap Spiritualitas Eskapis dalam 1 Korintus 15 - Rynaldi Mahardika Situmeang (Sekolah Tinggi Teologi Real Batam, 2025)
This article examines Paul’s correction of escapist spirituality in 1 Corinthians 15 by situating the doctrine of resurrection within the historical, cultural, and theological context of the Corinthian community. Influenced by Greek dualism, some believers rejected bodily resurrection and reinterpreted salvation as a purely spiritual reality detached from the body and history. Through an apologetic argument, Paul affirms the resurrection of Christ as a historical and eschatological event that constitutes the foundation of Christian faith and the guarantee of believers’ resurrection. The concept of soma pneumatikon underscores that resurrection does not abolish the body but entails an ontological transformation under the power of the Spirit. Within the framework of inaugurated eschatology, resurrection is presented as a reality already initiated in Christ while awaiting its final consummation. Consequently, resurrection functions as a theological correction to escapist, individualistic, and ahistorical forms of spirituality. Keywords: 1 Corinthians 15; new creation; Pauline eschatology; resurrection of the body; escapist spirituality Abstrak Artikel ini memperlihatkan koreksi Paulus terhadap spiritualitas eskapis dalam 1 Korintus 15 dengan menempatkan ajaran kebangkitan dalam konteks historis, kultural, dan teologis jemaat Korintus. Dipengaruhi oleh dualisme filsafat Yunani, sebagian jemaat menolak kebangkitan tubuh dan mereduksi keselamatan menjadi pengalaman rohani yang terlepas dari tubuh dan sejarah. Melalui argumentasi yang bersifat apologetik, Paulus menegaskan kebangkitan Kristus sebagai peristiwa historis dan eskatologis yang menjadi dasar iman Kristen serta jaminan kebangkitan orang percaya. Konsep soma pneumatikon menunjukkan bahwa kebangkitan bukan penghapusan tubuh, melainkan transformasi ontologis tubuh di bawah kuasa Roh. Dalam kerangka inaugurated eschatology, kebangkitan dipahami sebagai realitas yang telah dimulai di dalam Kristus sekaligus menantikan penggenapan akhir. Dengan demikian, kebangkitan berfungsi sebagai koreksi teologis terhadap spiritualitas yang eskapis, individualistik, dan a-historis. Kata kunci: 1 Korintus 15; ciptaan baru; eskatologi Paulus; kebangkitan tubuh; spiritualitas eskapis